Innovative Governance Strategy: Improving Community Welfare Through Regional Mutual Cooperation Empowerment Programs - Yudhi Lestanata; Cahyadi Kurniawan (Journal of Governance and Spatial Planning, 2025)
This study examines the innovative strategies implemented by the West Sumbawa Regency Government in improving community welfare through the Regional Empowerment Program for Mutual Cooperation, focusing on case studies in Seloto Village, Taliwang District, West Sumbawa Regency. This study aimed to analyze the effectiveness and impact of these innovative strategies in improving the welfare of village communities. This research method uses a mixed approach method that combines quantitative and qualitative analysis. Quantitative data were collected through questionnaires to village communities to measure the impact and effectiveness of the program. In contrast, qualitative data were obtained through in-depth interviews and observations to understand community perceptions, experiences, and program implementation. The study results indicate that the government's innovative strategies, including community involvement in program planning and implementation and local capacity development, have significantly contributed to improving welfare in Seloto Village. With the implementation of the intended program, it is evident from what is expected to run according to the wishes of the government, and obstacles in its implementation can be resolved together through meetings held with existing teams